Pertimbangan Jaksa dalam Tuntutan Pidana Mati Kasus Pembunuhan dan Pemerkosaan oleh Anak - Hanifa Saesti Handayani; Anis Widyawati (JURNAL HUKUM PELITA, 2025)
The prosecution of death penalty to children is a controversial issue and creates polemics in the juvenile criminal justice system because it violates the provisions of Article 3 letter f and Article 81 Paragraph (6) of the SPPA Law. This research aims to analyze the prosecutor's consideration in charging the death penalty against children who commit murder and rape based on the juvenile criminal justice system and identify the prosecutor's consideration in charging the death penalty against children who commit murder and rape based on legal objectives. This type of research is literature research (normative) with a statute approach and case approach. The data is analyzed descriptively qualitatively to provide an overview of the problems that occur systematically and accurately. The results showed that the main consideration of public prosecutors in handling juvenile criminal cases in Palembang still focuses on retributive punishment rather than rehabilitative punishment so that it is not in accordance with the juvenile criminal justice system and to realize the objectives of the law, the death penalty charges against children cannot be applied